1997
DOI: 10.3109/00016359709059205
|View full text |Cite
|
Sign up to set email alerts
|

Dental erosion associated with soft-drink consumption in young Saudi men

Abstract: This study reports on the causative factors of dental erosion in selected high- (n = 19) and low-erosion (n = 19) subgroups of a larger random sample (n = 95) of young male Saudi military inductees. By means of a questionnaire, the role of various possible factors related to oral health in general, and to dental erosion in particular, was assessed for each participant. Clinical examination included recordings of severity of dental erosion and fluorosis, presence of buccal cervical defects and first permanent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 34 publications
2
54
2
1
Order By: Relevance
“…However, Johansson et al reported a strong correlation between the presence of dental erosion and a high level of consumption of colatype and other soft drinks. 22 Milosevic et al 23,28 in two separate studies, found that frequent consumption of carbonated beverages and sport drinks was associated with tooth wear.…”
Section: Variable Significance (Sig)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, Johansson et al reported a strong correlation between the presence of dental erosion and a high level of consumption of colatype and other soft drinks. 22 Milosevic et al 23,28 in two separate studies, found that frequent consumption of carbonated beverages and sport drinks was associated with tooth wear.…”
Section: Variable Significance (Sig)mentioning
confidence: 99%
“…21 There have been significant associations shown between soft drink consumption and dental erosion. 13,22,23 Johansson et al reported a strong correlation between the presence of dental erosion and a high level of consumption of cola-type and other soft drinks. 22 Milosevic et al investigated various aetiological risk factors associated with tooth wear in 15-year-old children and concluded that frequent consumption of carbonated beverages is probably related to tooth wear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The frequent consumption of acidic drinks and foods cause extrinsic erosive lesions, which have been shown to be increasingly present in children [1] and young adults [2] with a high intake of acidic soft drinks.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found an association between the presence of dental erosion and a high level of consumption of cola-type and other fl avoured carbonated beverages. 7,9,12,13,[15][16][17] Many soft drinks contain phosphoric, citric and other acids as ingredients, and their pH is often less than 4.0. [18][19][20] Solid acidic candies also contain organic acids like citric acid, lactic and/or malic Objective To determine the erosive potential of seven different commercially available candy sprays in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%